Understanding the role of embedded relationships in the adoption of open standard interorganizational systems - Tsiga, Zayyad Danlami (2019)
Organizations today face a great challenge from the unpredictable, globalized and competitive business environment. One of the ways that organizations maintain competitiveness is by integrating their supply chains through the adoption of open standard interorganizational systems (OSIOS). Despite the benefits that have been promised in the case of OSIOS adoption, its adoption has recently slowed down and there are increased cases of failure in OSIOS adoption initiatives. This study examines various factors relating to the role of interorganizational relationships in the adoption of OSIOS among Chinese manufacturers.